2013
DOI: 10.1155/2013/945143
|View full text |Cite
|
Sign up to set email alerts
|

Garcinia indica as an Environmentally Safe Corrosion Inhibitor for Aluminium in 0.5 M Phosphoric Acid

Abstract: The Inhibitive and adsorption properties of aqueous extract of seeds of Garcinia indica extract (GIE) have been studied for corrosion control of aluminium in 0.5 M phosphoric acid solution using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques at 30 ∘ C to 50 ∘ C. The effects of inhibitor concentration on the inhibition action were investigated. Polarization measurements showed that the GIE acted as mixed inhibitor and the inhibitor molecules followed chemical adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The data was applied to various isotherms including Langmuir, Temkinand and Frumkin isotherms. It was found that the data best fits with Langmuir adsorption isotherm and can be represented by using the flowing relation [20].…”
Section: Adsorption Processmentioning
confidence: 81%
See 1 more Smart Citation
“…The data was applied to various isotherms including Langmuir, Temkinand and Frumkin isotherms. It was found that the data best fits with Langmuir adsorption isotherm and can be represented by using the flowing relation [20].…”
Section: Adsorption Processmentioning
confidence: 81%
“…The corrosion reaction of C.S. in sulphuric acidic media depends on temperature, the dependence of the rate constant k of corrosion process on the temperature T is the expressed by the Arrhenius law [20] how predicts that the corrosion rate increases with the temperature and E a and A may vary with temperature. The calculated values of activation energies ranged from 91.33 to 40.01 kJ•mol −1 in the presence and absence of inhibitor respectively.…”
Section: The Corrosion Processmentioning
confidence: 99%
“…The highmiddle frequencies time constant could be assigned to the charge transfer of the corrosion process and to the formation of a protective layer. Prabhu and Rao [49] indicated that the corrosion process of aluminum includes the formation of Al + ions at the metal/oxide interface and their migration through the oxide/solution interface where they are oxidized to Al 3+ , and, at the oxide/solution interface, OH − or O 2− ions are also formed. The fact that all the three processes are represented by only one time constant could be attributed either to the overlapping of the loops of processes or to the assumption that one process only dominates and, therefore, excludes the other processes.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…The capacitive semicircle at high-middle frequencies characterizes the active state of the interface when the Al is exposed to the sulfuric acid solution and it is related to the charge transfer of the corrosion process and the double layer behavior, and the inductive loop observed is attributed to the adsorption of species which promotes the corrosion rate [50]. In this case, the inductive loop may be related to the relaxation process obtained by adsorption and incorporation of ions and charged intermediates onto and into the oxide film [34,49]. Behavior described from EIS measurements is consistent with that observed in LPR measurements.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…In recent years, many alternative eco-friendly green corrosion inhibitors are developed, the range from inorganic (Kalyani and Rao, 2014;Gaun, 2007;Sribhurathy and Rejendran, 2012;Acharya et al, 2013) to organic compounds (Acharya et al, 2013;Sundaram et al, 2013;Merest et al, 2012;Afshari and Dehghanian, 2010;Zhang and Hua, 2009;Chandrasekar et al, 2006;Bekkouch, 2003). A lot of natural products were used as the corrosion inhibitors for different metals and alloys in various environments (Sundaram et al, 2013;Merest et al, 2012;Afshari and Dehghanian, 2010;Chandrasekar et al, 2006;Bekkouch, 2003;Negm et al, 2013;Sriram et al, 2014;Vasudha and Priya, 2014;Vastag et al, 2001;Li and Lei, 2011;Mahmoud, 2007;Prabhu and Rao, 2013). Similalry, inorganic compounds are also widely used as effective corrosion inhibitors to control the corrosion Research Article rate of metallic materials in corrosive environments.…”
Section: Introductionmentioning
confidence: 99%